Biology and natural enemies of Cydalima perspectalis in Asia: Is there biological control potential in Europe?. (22nd April 2014) - Wan, H.; Haye, T.; Kenis, M.; Nacambo, S.; Xu, H.; Zhang, F.; Li, H.
Abstract The box tree moth, Cydalima perspectalis (Walker) (Lepidoptera: Crambidae), a native pest of box trees (Buxus spp.) in Asia, was first detected in Germany and the Netherlands in 2007 and has since rapidly spread throughout Europe causing severe damage to ornamental and native box trees. To date, sustainable control strategies for C. perspectalis in Europe are lacking, primarily owing to the inadequate information regarding the biology and the ecology of this recent invader. Several studies conducted in Asia, however, may provide important information for the development of management strategies against C. perspectalis, which are urgently needed to preserve the natural box tree forests in Europe. The current literatures on the biological characteristics, host plants, phenology, distribution and control options of the box tree moth in Asia are reviewed, preliminary data on the parasitism of C. perspectalis in Europe are provided, and options for sustainable long‐term solutions for the management of the invasive pest in Europe are discussed.